2018
DOI: 10.1093/molehr/gay008
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking physiological O2 tension in the female reproductive tract improves assisted reproduction outcomes in pig

Abstract: This study was funded by Spanish Ministry of Economy and Competitiveness (MINECO) and European Regional Development Fund (FEDER). Grants AGL2012-40180-C03-01 and AGL2015-66341-R. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Thus, we assume this was the reason for the higher pregnancy and parturition outcomes obtained here. Also the use of a minimally invasive procedure based on a LESS approach might have in uenced positively the pregnancy rate because, as demonstrated in previous works [29,30], the trauma to the uterus was minimal and the full recovery of the animal after procedure signi cantly reduced compared to laparotomy. Despite this, the percentage of non-pregnant animals after embryo transfer in our study was still higher than 64% in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we assume this was the reason for the higher pregnancy and parturition outcomes obtained here. Also the use of a minimally invasive procedure based on a LESS approach might have in uenced positively the pregnancy rate because, as demonstrated in previous works [29,30], the trauma to the uterus was minimal and the full recovery of the animal after procedure signi cantly reduced compared to laparotomy. Despite this, the percentage of non-pregnant animals after embryo transfer in our study was still higher than 64% in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…However, most of the genes belonging to the former ontology group were upregulated after the 7 days days of culture, when compared with the first day. This may be due to the cell exposure to atmospheric oxygen tension, which is much higher than in oviduct, and may cause excessive ROS accumulation in culture medium in vitro [26].…”
Section: Discussionmentioning
confidence: 99%
“…After fertilization, the embryos are cultured at 38.5°C in a humidified atmosphere of 5% CO 2 in air overnight, and then the next day (Day 1), they are moved to a humidified atmosphere of low oxygen (5% O 2 , 5% CO 2 , and 90% N 2 ) until Day 6 (Chen et al, ). Recently, García‐Martínez et al () demonstrated that the use of the same O 2 conditions as those found in the pig reproductive tract (7% O 2 during IVF and embryo culture) were beneficial for embryo production in vitro.…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 99%
“…Recently, García-Martínez et al (2018) demonstrated that the use of the same O 2 conditions as those found in the pig reproductive tract (7% O 2 during IVF and embryo culture) were beneficial for embryo production in vitro.…”
Section: Transcriptomic and Metabolomic Approaches To Understand Prmentioning
confidence: 99%